2014
DOI: 10.1155/2014/741452
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Subjective Tinnitus

Abstract: Tinnitus is one of the major audiological diseases, affecting a significant portion of the ageing society. Despite its huge personal and presumed economic impact there are only limited therapeutic options available. The reason for this deficiency lies in the very nature of the disease as it is deeply connected to elementary plasticity of auditory processing in the central nervous system. Understanding these mechanisms is essential for developing a therapy that reverses the plastic changes underlying the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 133 publications
0
25
0
Order By: Relevance
“…Whether an animal develops tinnitus or not seems to be not directly correlated with the degree of hearing loss either immediately after the acoustic trauma exposure or a few months later [see Ref. ( 27 ) for a review]. In the present study, all of our rats exhibited elevated ABR thresholds across a range of frequencies immediately after the acoustic trauma.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Whether an animal develops tinnitus or not seems to be not directly correlated with the degree of hearing loss either immediately after the acoustic trauma exposure or a few months later [see Ref. ( 27 ) for a review]. In the present study, all of our rats exhibited elevated ABR thresholds across a range of frequencies immediately after the acoustic trauma.…”
Section: Discussionmentioning
confidence: 48%
“…It has been shown that not every animal exposed to acoustic trauma develops tinnitus, with the reported tinnitus-induction rate varying from 30 to 80% [see Ref. ( 27 ) for a review]. Whether an animal develops tinnitus or not seems to be not directly correlated with the degree of hearing loss either immediately after the acoustic trauma exposure or a few months later [see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous confounding effects of noise exposure could have also controlled their behavior, such as unilateral hearing loss, hyperacusis, motoric changes, generalized hyperactivity, stress, and anxiety. The following validation experiments are proposed to confirm or deny our hypothesis that the abnormal behavior of the affected group is due to tinnitus ( 42 44 ): Measuring corticosterone levels before behavioral testing can determine whether there is a correlation between stress and spontaneous behavior in noise and silence. Inducing stress in normal-hearing animals before behavioral testing may show the effects of stress and anxiety on the behavior of guinea pigs in noise and silence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this high prevalence and the tinnitus-associated distress of affected patients, which in severe cases may experience insomnia, psychological disorders like depression, the inability to work, or even commit suicide (Coles, 1984 ; Lewis et al, 1994 ; Langguth et al, 2011 ), there still is no effective cure for the condition, because all tinnitus research faces one central problem: Whereas the existence of a tinnitus percept can unequivocally be determined in human patients (one can simply ask them; cf. e.g., Pantev et al, 2012 ; Elgoyhen et al, 2015 ; Husain, 2016 ; Leaver et al, 2016 ), this is only unsatisfactorily possible in animal models for tinnitus (Von Der Behrens, 2014 ; Zhang et al, 2014 ; Galazyuk and Hebert, 2015 ; Brozoski and Bauer, 2016 ). On the other hand, the exact mechanisms within the auditory system that lead to the development of tinnitus are still unknown and hard to identify, since invasive neurophysiological methods that are essential for such research are only available in animal models but not in humans.…”
Section: Introductionmentioning
confidence: 99%